Модификация микропрограммного автомата с операционным автоматом переходов и заменой входных переменных - Бабаков, Р.М.; Баркалов, А.А. (Управляющие системы и машины, 2017)
Предложено новое структурное решение, способствующее снижению аппаратурных затрат в логической схеме микропрограммного автомата с операционным автоматом переходов. Наряду с методом замены входных переменных используется метод сопоставления операций переходов состояниям автомата, что позволяет добиться одновременного снижения аппаратурных затрат в операционном автомате переходов и схеме формирования кодов операций. Определено условие эффективности предложенной структуры автомата в сравнении со структурами-прототипами. Запропоновано нове структурне рішення, яке сприяє зниженню апаратурних витрат у логічній схемі мікропрограмного автомата з операційним автоматом переходів. Поряд з методом заміни вхідних змінних використовується метод зіставлення операцій переходів станам автомата, що дозволяє домогтися одночасного зниження апаратурних витрат в операційному автоматі переходів і схемі формування кодів операцій. Визначено умову ефективності запропонованої структури автомата в порівнянні зі структурами-прототипами. Purpose. The purpose of this article is to research a new way for hardware expenses optimization in logical circuit of finite state machine with datapath of transitions. Methods. It is proposed to use in one structure of finite state machine simultaneously two known methods for hardware expenses optimization. The method of comparing the codes of transition operations to the FSM states makes it possible to reduce the complexity of the circuit of the operation codes formation by reducing the number of input signals. The method of replacement of input variables makes it possible to reduce the complexity of the datapath of transitions by reducing the number of functional blocks. Results. A new modification of the microprogram finite state machine structure with datapath of transitions and replacement of input variables is proposed. The peculiarity of this structure is the lower hardware expenses in the logical circuit of finite state machine in comparison with the prototype structures. The general condition of the effectiveness of this structure by the criterion of hardware expenses is determined.